Perceived influences of fruit and vegetable consumption among Indian adolescents – A qualitative inquiry - Neha Rathi; Anthony Worsley; Meg Bruening (BMC Public Health)
Abstract Background Fruits and vegetables are primary sources of vitamins and minerals that may alleviate the risk of chronic illnesses. However, Indian adolescents consume inadequate amounts of fruits and vegetables, with less than 10% meeting recommendations. Micronutrient deficiencies are a major public health problem in India. For example, the prevalence of iron-deficiency anemia and Vitamin A deficiency in adolescents is 28.5% and 14.4%, respectively. To promote fruit and vegetable consumption among Indian adolescents, we need to identify the factors which may influence the consumption. The aim of this qualitative inquiry was to explore perceived influences of fruit and vegetable consumption among Indian adolescents. Methods Using purposive sampling, adolescents aged 10–19 years were recruited from two public and two private (independent) schools in Varanasi, India. Face-to-face interviews along with the ‘draw and tell’ technique were used for data collection. Interviews were conducted in English as well as in Hindi depending on the preferences of the adolescents. The conversations were digitally recorded and transcribed verbatim. The transcribed data were subjected to thematic analysis. Data were coded inductively, and themes were extracted using NVivo software program. Results A total of 58 adolescents (53% female; 74% urban) with mean age 13.6 years completed the interviews. Nine major themes and associated sub-themes emerged, including: (i) Sensory properties (i.e., taste, color, flavor, texture); (ii) Health and immunity; (iii) Allergy; (iv) Home food environment (i.e., influence of mothers, availability and accessibility of fruits and vegetables); (v) Cost; (vi) Food preparation; (vii) Influence of peers; (viii) School food environment; (ix) Proclivity for energy-dense, nutrient-poor foods and beverages. Conclusions The emerging themes and sub-themes show that multiple factors are likely to affect fruit and vegetable consumption in adolescents, aligning with literature on adolescent fruit and vegetable consumption in international settings. Behavioral interventions should be designed to create enabling environments to encourage fruit and vegetable consumption in Indian adolescents by removing barriers at the individual, household, and community levels, thereby reducing the enduring prevalence of micronutrient deficiencies.